High Energy Parametric Laser Source and Frequency-Comb-Based Wavelength Reference for CO2 and Water Vapor DIAL in the 2 µm Region: Design and Pre-Development Experimentations - Jonas Hamperl; Jan Fabian Geus; Kjell M. Mølster; Andrius Zukauskas; Jean-Baptiste Dherbecourt; Valdas Pasiskevicius; Lukas Nagy; Oliver Pitz; David Fehrenbacher; Hanjo Schaefer; Dirk Heinecke; Michael Strotkamp; et al. (Atmosphere, 2021)
We present a differential absorption lidar (DIAL) laser transmitter concept designed around a Nested Cavity Optical Parametric Oscillator (NesCOPO) based Master Oscillator Power Amplifier (MOPA). The spectral bands are located around 2051 nm for CO2 probing and 1982 nm for H216O and HD16O water vapor isotopes. This laser is aimed at being integrated into an airborne lidar, intended to demonstrate future spaceborne instrument characteristics: high-energy (several tens of mJ nanosecond pulses) and high optical frequency stability (less than a few hundreds of kHz long term drift). For integration and efficiency purposes, the proposed design is oriented toward the use of state-of-the-art high aperture periodically poled nonlinear materials. This approach is supported by numerical calculations and preliminary experimental validations, showing that it is possible to achieve energies in the 40–50 mJ range, reaching the requirement levels for spaceborne Integrated Path Differential Absorption (IPDA) measurements. We also propose a frequency referencing technique based on beat note measurement of the laser signal with a self-stabilized optical frequency comb, which is expected to enable frequency measurement precisions better than a few 100 kHz over tens of seconds integration time, and will then be used to feed the cavity locking of the NesCOPO.